International technology transfer, firm productivity and employment - Pantea, Smaranda (2012)
This dissertation contributes to the empirical literature on the effects of international technology transfer on firms' productivity and employment in developing and transition countries. It combines three empirical essays which provide evidence on how participation in international activities affects firms' productivity, how it interacts with firms' absorptive capacity and how it affects firms' demand for skilled labour in 26 transition countries in Europe and Central Asia (ECA) region.